Maternal Conceptions in Classical Literature and Philosophy. - Sharrock, Alison; Keith, Alison (Toronto : University of Toronto Press, 2020)
This book explores motherhood in Greek and Roman literature, focusing on images of mothers and their relationships with their children across a variety of genres.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books